School principals managerial leadership strategies in increasing students' digital literacy - Afif Abdurrohman, Muhammad; Hidayati , Dian (Universitas Ahmad Dahlan, 2024)
Digital literacy is an essential skill that allows students to understand, use, and effectively participate in the digital world. Moreover, it enables them to explore, understand, and develop the skills necessary for using technology wisely and critically evaluating information. This research aims to ascertain the managerial leadership strategies employed by school principals to enhance students' digital literacy. Specifically, it focuses on such strategies in the context of school leadership. Research into school principal leadership strategies for enhancing students' digital literacy holds significance due to the pivotal role of leadership in optimizing school management, particularly in advancing students' digital literacy. Additionally, this research holds promise for contributing to the field of education and serving as a valuable reference for other school principals. Employing a qualitative approach, this research collected data through interviews and document analysis of school archives. The respondents interviewed included the principal and teachers of MBS Prambanan Elementary School. Data analysis followed the Miles and Huberman approach, encompassing data collection, reduction, presentation, and verification or conclusion drawing. The study identified managerial leadership strategies utilized by the principal of Muhammadiyah Boarding School Prambanan to enhance students' digital literacy. These strategies include (1) fostering collective collegial leadership, (2) provisioning facilities related to digital technology, (3) fostering learning innovations, (4) cultivating a culture of digital literacy and guidance for students, and (5) conducting evaluations.